(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Quality control is an important issue in the ceramic tile industry. Price of ceramic tiles also depends on purity of texture, accuracy of color, shape etc. Considering this criteria, an integratedÂ defect detection and classification technique has been proposed which plays an important role in ceramic tiles industries to detect the defects and to control the quality of ceramic tiles.GLCM extracts theÂ texture features and these featuresÂ together with color features are used for analysis in classifiers such as SVM, KNN and Bayesian. Experimental results illustrated thatÂ every classifier gives highest accuracy with HSV.